Eugenio Ímaz Echeverría (1900-1951) y la herencia del romanticismo político alemán. - LEMKE DUQUE, CARL ANTONIUS (Anuario Filosófico, 2019)
This paper delves into the sociopolitical concepts of Eugenio Ímaz Echeverría previous to the outbreak of the Spanish Civil War in 1936. The following topics are examined: (a) the context of his academic and intellectual socialization; his writings during this period, including (b) translations and (c) prefaces, reviews and essays; and, fi nally, (d) the basic character of this work considered as a political philosophy. The contribution of the present study is to consider Ímaz's intellectual work as a catalyst for a certain type of political ontology which can be classified as left-wing romantic decisionism.